Relatório de Estágio Profissional - "A utopia que se tornou realidade" - Flávio Agostinho Teixeira Coelho (2018)
The internship represented, to me as a intern, a very significant part of what my learning process was, throughout all my education, since it was possible to put into practice everything I have learned in theory.This last stage made me confront with the true reality of school, perceive all the difficulties and challenges that a teacher faces in his daily life, however this period made me understand with more clarity how rich the job is, and through this document called the Internship Report, I try to explain exactly that. In terms of its organization, this document is divided into six main groups: the first one refers to the "Introduction"; the second makes a small "Personal Framing" of what I am as a person out of school, regarding my sporting experiences, family background, options in academic and school life as well as my expectations for this moment that I now describe;the third "Institutional Framing" refers to how this stage was organized, characterizing from the school to the students, who directly worked with me; the fourth concerns the "operational framing", being subdivided into three areas: Area 1 - Organization and Management of Teaching and Learning, here was compressed everything that was related to teach planning, its realization and evaluation; Area 2 - School participation and Interaction with the community, here is a brief description of how I interacted with the school community as well as what activities outside the classroom context I was inserted in; Area 3 - Professional Development, showing what was decisive in my learning process. The fifth point reflects the Case Study with the theme "Improving self-esteem through increased skills in Physical Education". The last large group concerns the "Conclusion", in the same is exposed a reflection on this school year stuffed with great experiences.